(untitled) (Portuguese Journal of Family Medicine and General Practice, 2014)
Incest is a public health problem with low visibility. It is under diagnosed by health services. It is often unreported. Conviction rates are low because disclosure by the victim is essential and is rare and difficult. The family physician is in a privileged position to approach this issue. This case report describes a 39 year old woman who was raised by a foster family from 6 months of age until the age of 7. She maintained contact with her biological family and was the victim of incest by her older brother until she was 17. This case describes the lengthy process of disclosure and the associated legal and ethical issues. The patient demonstrated borderline personality disorder, post-traumatic stress disorder, and family and social dysfunction. Therapy in these cases is prolonged, multidisciplinary and comprehensive, including individual and family therapy. The family physician may adopt an empathic attitude, allowing the patient to recognize that their maladaptative emotions are a survival response to incest in the past.